Knowledge and Practice of Dietary Recommendations among Cardiovascular Disease Patients Attending Ngaoundere Regional Hospital, Adamawa Region, Cameroon - M. Pancha, Olivier; T. Tamanji, Marcel; Mtsavara, Josep; S.B. Bouagni, Laure; O. Ngoufack, Jacques; Tchiegang, Clergé (Journal of Nutritional Therapeutics, 2017)
Objective: To assess the level of awareness and adherence of patients to dietary recommendations in the management of Cardiovascular Diseases (CVDs). Methods: This cross-sectional study included CVD patients on medical visits at the cardiology unit of Ngaoundere Regional Hospital. Well informed and consenting participants filled a pre-tested questionnaire on dietary knowledge and practice. Results: 129 patients were retained in this study out of 151 enrolled. 58.9% of participants knew that the consumption of vegetables is beneficial for their status. Fruit consumption recorded the same level of awareness. All other dietary variables studied revealed less than 50% level of awareness among participants. Concerning recommended dietary practices, 73.64% of participants consumed oils rich in saturated fatty acids. Meat and fish consumption were recorded at 62.01% and 65.12% respectively, with a 94.57% preference to red meat consumption. Almost 19.38% of the study population consumed eggs more than 3 times per week, 31.78% and 41.09% consumed vegetables and fruits at least thrice and twice a week respectively. The overall mean adherence to the studied cardiovascular disease dietary recommendations was 38.31%, with only fish, vegetable and tea/coffee recommendations recording adherences of 50% and above. Conclusion: The findings demonstrate a low level of awareness and adherence to dietary recommendations in the management of CVDs, thus the need for the strengthening of health promotion programs and improvement of the nutritional advices in our context.